Procalcitonin as a Diagnostic and Monitoring Tool for Bacteraemia in Patients on Haemodialysis: A Systematic Review - Aniebiot-Abasi Udofia; Yiwei Zhang (Kidney and Dialysis)
Background: Infections are a major cause of mortality in haemodialysis patients. The increasing antimicrobial resistance globally further exacerbates this concern. Procalcitonin has shown potential in aiding antimicrobial stewardship and reducing the mortality and morbidity associated with infections. This systematic review aims to synthesise the existing literature on the utility of procalcitonin as a diagnostic and monitoring tool for haemodialysis patients with suspected bacteraemia. Methods: Multiple electronic databases (EMBASE, MEDLINE, and the Cochrane Library) were systematically searched to identify primary studies evaluating procalcitonin use in haemodialysis patients with suspected bacteraemia. Using a narrative synthesis approach, along with other quality assessment tools, recommendations regarding procalcitonin usage in dialysis were formulated. Results: Eleven studies were identified. The review proposes a procalcitonin-guided antibiotic protocol aimed at facilitating antibiotic use in haemodialysis patients with suspected bacteraemia. Caution is, however, advised against relying solely on procalcitonin for diagnosis, emphasising the integration of procalcitonin with other clinical and biomarkers of infection. Conclusions: Procalcitonin shows promise as a valuable diagnostic and monitoring tool for suspected bacteraemia in haemodialysis patients. While caution is advised against relying solely on PCT for diagnosis, its integration with other clinical indicators can enhance infection management. To fully establish its clinical utility, more research is needed.